شعرية الأسلوب في قصيدة "يا ابنتي" للشاعر سعد - مشارة، حسين; باسي، عفاف; خوازم، مباركة; خوازم، مريم (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى الكشف عن السمات الفنية وشعرية الأسلوب, التي انعكست في قصيدة "يا ابنتي" للشاعر "سعد مردف", ولقد اعتمدنا في بحثنا هذا على المنهج الوصفي والتحليل الأسلوبي, أما الاشكالية فتمثلت في التساؤلات الآتية: ما هي شعرية الأسلوب؟ وكيف تجلت في النص؟ وماهي أهم المستويات التي تأسس عليها النص الشعري في قصيدة "يا ابنتي" للشاعر سعد مردف؟ ولقد خلصت الدراسة الى أن الأسلوبية تهتم بتحليل مستويات الخطاب, ويعتبر الشاعر سعد مردف الجزائري شاعر معاصر وتتناول أشعاره أغراض متعددة, كما يعد الشعر عنه صناعة تبنى على جملة من المعطيات أهمها ما كان قائما على الممارسة والتجربة, ولقد اعتمد الشاعر في قصيدة " يا ابنتي" على نمط القصيدة العمودي, كما توصلت الدراسة إلى إن الإيقاع أعم من التوازن باعتباره يشمل مختلف تشكيلات القصيدة أما الوزن فهو جزء منه, كما إن الإيقاع نوعان إيقاع داخلي وإيقاع خارجي. وما يلحظ أن الشاعر نظم القصيدة على بحر الخفيف وقد وفق في ذلك لأنه الملائم للتعبير عن الحزن والرثاء, واعتمد على روي واحد وهو صوت النون المجهور الأنفي المنفتح واستخدمه كوسيلة لإثارة الإيقاع والنغم. The study aimed to reveal the artistic and poetic features of style, which were reflected in the poem “Oh My Daughter” by the poet “Saad Mirdif”. In our research, we relied on the descriptive approach and stylistic analysis, while the problem was represented in the following questions: What is the poetics of style? How did it appear in the text? What are the most important levels on which the poetic text is based in the poem “Ya Daughter” by the poet Saad Mardif? The study concluded that stylistics is concerned with analyzing the levels of discourse. The poet Saad Mirdif Al-Jazairi is considered a contemporary poet and his poems address multiple purposes. Poetry about him is also an industry built on a number of data, the most important of which is what was based on practice and experience. The poet relied in the poem “Oh My Daughter” Regarding the vertical style of the poem, the study also concluded that rhythm is more general than balance as it includes the various formations of the poem, but the meter is part of it, and rhythm is of two types, internal rhythm and external rhythm. What is notable is that the poet composed the poem on Bahr al-Khafif, and he succeeded in doing so because it is appropriate for expressing sadness and lamentation. He relied on one narrator, which is the open, nasal voice of the Nun, and used it as a means to stimulate rhythm and melody.